2021
DOI: 10.1101/2021.10.15.461205
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Into the range: a latitudinal gradient or a center-margins differentiation of ecological strategies in Arabidopsis thaliana?

Abstract: Background and Aims: Determining within-species large-scale variation in phenotypic traits is central to elucidate the drivers of species ranges. Intraspecific comparisons offer the opportunity to understand how trade-offs and biogeographical history constrain adaptation to contrasted environmental conditions. Here we test whether functional traits, ecological strategies and phenotypic plasticity in response to abiotic stress vary along a latitudinal or a center- margins gradient within the native range of Ara… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 110 publications
2
6
0
Order By: Relevance
“…Indeed, accessions originating from colder environments show increased freezing tolerance upon cold acclimation (4952). This fits with observations of northern and colder regions favoring slower growing, more stress-tolerant plants (3, 4). Also biogeographic studies in A. thaliana found that winter temperatures are a major determinant of suitable habitats for this species (5355).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, accessions originating from colder environments show increased freezing tolerance upon cold acclimation (4952). This fits with observations of northern and colder regions favoring slower growing, more stress-tolerant plants (3, 4). Also biogeographic studies in A. thaliana found that winter temperatures are a major determinant of suitable habitats for this species (5355).…”
Section: Discussionsupporting
confidence: 91%
“…These strategies have evolved to maximize fitness, but are constrained by trade-offs between components such as growth, survival and reproduction (1, 2). While most life-history studies investigate differences between species, there is also variation found within species, including in Arabidopsis thaliana , where life-history variation has been linked to climate parameters (35). Less clear is how trade-offs are shaping this variation.…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, DeLeo et al (2020) found region-specific decadal shifts in phenology and physiology in herbarium specimens. Public seed banks house great diversity from across species ranges that can also be used to study the geography of natural variation (Estarague et al, 2021; Scholl et al, 2000). Here we use individual-level performance estimates from museum specimens and life history variation in natural seedbank accessions to interrogate predictions from fitted distribution models.…”
Section: Introductionmentioning
confidence: 99%
“… Plant survival has two categories (dead or alive), which were measured according to the protocol described in Estarague et al (2021) . Genotypes have 10 categories corresponding to the 10 natural accessions used here.…”
Section: Nirs Quantifies Functional Trait Variability and Summarizes ...mentioning
confidence: 99%
“…To further explore the potential of NIRS as a predictive tool of plant stress level, we used experimental data included in our database ( Supplementary Material ) from 30 genotypes of Arabidopsis thaliana subjected to water deficit combined with either high or low (freezing) temperatures ( Estarague et al, 2021 ). All plant individuals were measured for leaf NIRS in the course of the treatment, and survival was visually recorded after the treatment.…”
Section: Measuring Plant Responses To the Environment With Nirsmentioning
confidence: 99%